Case report: supporting students with assessment by replicating open-door tutorials in online distance education – the student experience - Townsend, Maria; Champion, Emma; Berndt, Gwendoline (Open learning, 2025)
Standard online tutorials at The Open University, based in the UK, are generally tutor-led with the tutor setting the agenda and content. This study investigated the inclusion of online student-led drop-in tutorials to support assessment on an OU level one module. The aims were to gauge the value to students of this style of tutorial, to understand their behaviour during the sessions and to assess their overall experience. Data were collected via two student surveys, confidence polls at the end of each tutorial and one student-led focus group. Other evidence used included attendance data and student achievement on the module. Twenty-three percent of the cohort attended at least one drop-in session. The students surveyed indicated that this style of tutorial was a valuable addition to the overall tuition strategy. The majority arrived at the start of each session and stayed until the end, rather than ‘dropping in and out’. Most reported that listening to questions from other students was useful, even if they had no question of their own to ask. The overall findings were that students value this style of tutorial. Those who attended reported increased confidence in subsequently completing assignments. There were also some indications that attendees gained higher assessment scores.